Effects of depressive symptoms on antecedents of lapses during a smoking cessation attempt: an ecological momentary assessment study. (23rd May 2014) - Brodbeck, Jeannette; Bachmann, Monica S.; Brown, Anna; Znoj, Hans Joerg
Abstract Aims To investigate pathways through which momentary negative affect and depressive symptoms affect risk of lapse during smoking cessation attempts. Design Ecological momentary assessment was carried out during 2 weeks after an unassisted smoking cessation attempt. A 3‐month follow‐up measured smoking frequency. Setting Data were collected via mobile devices in German‐speaking Switzerland. Participants A total of 242 individuals (age 20–40, 67% men) reported 7112 observations. Measurements Online surveys assessed baseline depressive symptoms and nicotine dependence. Real‐time data on negative affect, physical withdrawal symptoms, urge to smoke, abstinence‐related self‐efficacy and lapses. Findings A two‐level structural equation model suggested that on the situational level, negative affect increased the urge to smoke and decreased self‐efficacy (β = 0.20; β = −0.12, respectively), but had no direct effect on lapse risk. A higher urge to smoke (β = 0.09) and lower self‐efficacy (β = −0.11) were confirmed as situational antecedents of lapses. Depressive symptoms at baseline were a strong predictor of a person's average negative affect (β = 0.35, all P < 0.001). However, the baseline characteristics influenced smoking frequency 3 months later only indirectly, through influences of average states on the number of lapses during the quit attempt. Conclusions Controlling for nicotine dependence, higher depressive symptoms at baseline were associated strongly with a worse longer‐term outcome. Negative affect experienced during the quit attempt was the only pathway through which the baseline depressive symptoms were associated with a reduced self‐efficacy and increased urges to smoke, all leading to the increased probability of lapses.